# Triangular Prism

Written by Jerry Ratzlaff on . Posted in Solid Geometry

## Edge formula

$$a = \frac {A_l } {h} - b-c$$

$$b = \frac {A_l } {h} - a-c$$

$$c = \frac {A_l } {h} - a-b$$

Where:

$$a$$ = edge

$$b$$ = edge

$$c$$ = edge

$$h$$ = height

$$A_l$$ = lateral surface area

## Height formula

$$h = \frac {A_l } {a+b+c }$$

Where:

$$h$$ = height

$$A_l$$ = lateral surface area

$$a$$ = edge

$$b$$ = edge

$$c$$ = edge

## Base Area formula

$$A_b = \frac {1}{4} \sqrt { -b^4 + 2 \left( b c \right)^2 +2 \left( b a \right)^2 -c^4 +2 \left( c a \right)^2 -a^4 }$$

Where:

$$A_b$$ = base area

$$a$$ = edge

$$b$$ = edge

$$c$$ = edge

## Lateral Surface Area formula

$$A_l = \left( a+b+c \right) h$$

Where:

$$A_l$$ = lateral surface area

$$a$$ = edge

$$b$$ = edge

$$c$$ = edge

$$h$$ = height

## Volume formula

$$V = \frac {1}{4} h \sqrt { -b^4 + 2 \left( b c \right)^2 +2 \left( b a \right)^2 -c^4 +2 \left( c a \right)^2 -a^4 }$$

Where:

$$V$$ = volume

$$a$$ = edge

$$b$$ = edge

$$c$$ = edge

$$h$$ = height